2017
DOI: 10.1039/c7ta04406b
|View full text |Cite
|
Sign up to set email alerts
|

Highly porous carbon nanofibers co-doped with fluorine and nitrogen for outstanding supercapacitor performance

Abstract: One-dimensional nitrogen and fluorine co-doped mesoporous carbon nanofibers (NFMCNFs) were fabricated for energy storage electrodes with high specific capacitance and long-term cycle stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(103 citation statements)
references
References 50 publications
3
96
3
1
Order By: Relevance
“…These are higher than the previous studies reported, [62][63][64][65][66] such as Co 9 S 8 //AC. NC@CoSe 2 //Co-NC@Fe 2 O 3 shows the maximum power density of 8.9 kW/kg at an energy density of 14 Wh/kg.…”
Section: Electrochemical Propertiescontrasting
confidence: 70%
“…These are higher than the previous studies reported, [62][63][64][65][66] such as Co 9 S 8 //AC. NC@CoSe 2 //Co-NC@Fe 2 O 3 shows the maximum power density of 8.9 kW/kg at an energy density of 14 Wh/kg.…”
Section: Electrochemical Propertiescontrasting
confidence: 70%
“…Moreover, the two peaks became broaden with the increase of temperature, indicating the amorphous properties of these materials . Raman spectra is widely used to analyse the structural vibration and graphitisation degree of carbon materials . D‐peak near 1329 cm −1 representing the lattice defects of C atom and G‐peak is about 1583 cm −1 referring to the in‐plane stretching vibration of sp 2 hybridization of C atoms .…”
Section: Results and Discussiontextural And Structural Propertiesmentioning
confidence: 88%
“…As shown in Figure f, the ‘C s ’ of D‐graphene at 2, 3, and 5 A g −1 are 158, 125, and 92 F g −1 , respectively. The D‐graphene supercapacitor electrode offers high ‘C s ’ than that of some of the recently reported supercapacitors . As exhibited in Figure g, the Ragone plot of the D‐graphene supercapacitor electrode at three different current densities offered the highest ‘E’ of 22 Wh kg −1 and ‘P’ of 500 W kg −1 .…”
Section: Resultsmentioning
confidence: 99%